2015
DOI: 10.1001/jamasurg.2014.3852
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Results of a Magnetic Resonance Imaging–Based Swedish Screening Program for Individuals at Risk for Pancreatic Cancer

Abstract: During a median follow-up of approximately 1 year, pancreatic lesions were detected in 40% of the patients, of whom 5 underwent surgery. Although the study time was relatively short, the surveillance program in individuals at risk seems to be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 33 publications
(25 reference statements)
0
56
0
1
Order By: Relevance
“…as magnetic resonance imaging, should be performed. 27,28 Several studies have shown that elevated ALP is a common marker for diagnosing gallstone-induced pancreatitis. 16,18 Several recent reports proposed that the ALT level might be a marker for early recognition of a gallstone etiology in patients with AP.…”
Section: 2412mentioning
confidence: 99%
“…as magnetic resonance imaging, should be performed. 27,28 Several studies have shown that elevated ALP is a common marker for diagnosing gallstone-induced pancreatitis. 16,18 Several recent reports proposed that the ALT level might be a marker for early recognition of a gallstone etiology in patients with AP.…”
Section: 2412mentioning
confidence: 99%
“…Additionally, the results of 3 large cohort studies have been released since Lu's publication. 7,10,11 This study aims to estimate the diagnostic yield of abdominal imaging for pancreatic cancer screening in HRI based on existing literature. We estimated detection rates of high-risk lesions using 2 different imaging strategies (EUS or MRI) and compared imaging findings among different HRI groups.…”
mentioning
confidence: 99%
“…104 A recent Swiss study of MR-based pancreatic cancer screening in high-risk individuals similarly detected pancreatic lesions in 40% of individuals. 105 Within this study, 12.5% of patients underwent pancreatic resection due to abnormalities seen on screening, and 7.5% of the cohort was found to have resectable adenocarcinoma. 105 …”
Section: Hereditary/familial Pancreatic Cancermentioning
confidence: 78%
“…105 Within this study, 12.5% of patients underwent pancreatic resection due to abnormalities seen on screening, and 7.5% of the cohort was found to have resectable adenocarcinoma. 105 …”
Section: Hereditary/familial Pancreatic Cancermentioning
confidence: 78%